Analisis Tingkat Kepuasan Konsumen Terhadap Kualitas Ikan Bandeng dan Pelayanan Pada Pemancingan ‘Lagoona’ Kabupaten Sidoarjo - Diza, Andhika Nararya; Indah, Pawana Nur; Syah, Mirza Andrian (Universitas Galuh, 2024)
The global economic crisis that is hitting us has resulted in many service companies taking the initiative to do various things to ensure that the company continues to run well and still prioritizes the concept of customer satisfaction and service quality. This is known as a factor that influences the success of a company, so customer service and satisfaction are vital aspects in maintaining a business and winning the competition. This research aims to analyze the level of consumer satisfaction with the quality of milkfish and service to consumers and to analyze the attributes of the quality of milkfish and service at Lagoona Fishing, Sidoarjo Regency which need to be improved to increase consumer satisfaction. Sample determination methodaccidental sampling with a total of 100 respondents. Collecting primary data by means of interviews assisted by using questionnaires. The first objective was analyzed using CSI analysis (Customer Satisfaction Index) and the second objective is analyzed using IPA Analysis (Importance Performance Analysis). The research results show that in general lagoona fishing customers are in the satisfied category with a CSI value of 78.67%. Meanwhile, the main priorities for improvement include: service time, waiter response time to customers, problem handling, guidance assistance, accurate information, condition of the fishing pond, cleanliness of the place, availability of additional supporting facilities and attributes that are considered important and need to be maintained include: availability fish, quality of milkfish, friendly and patient attitude, willingness to explain and parking access.